Anatomically‐based transoral surgical approach to early‐stage oral tongue squamous cell carcinoma. Issue 5 (30th January 2020) - Calabrese, Luca; Pietrobon, Giacomo; Fazio, Enrico; Abousiam, Monir; Awny, Shadi; Bruschini, Roberto; Accorona, Remo
Abstract: The mainstream of treatment of early‐stage oral tongue squamous cell carcinoma (OTSCC) is represented by transoral resection with "adequate" free margins. Despite that, a precise and shared definition of "adequate margin" is lacking, and so is a standardized transoral surgical technique.The tongue is a symmetrically paired organ, consisting of intertwining intrinsic and extrinsic muscles, which can be distinguished during dissection. Routes of tumoral spread in oral tongue cancer are well‐known and should be taken into account during resection. We propose herein a standardized and replicable surgical technique to resect early‐stage OTSCC, based on rational anatomical considerations.